12High density lipoproteins exert pro-inflammatory effects on macrophages via IKK2- and NIK-independent NF-kB activation. (15th July 2014) - Van Der Vorst, EPC; Theodorou, K; Plat, J; Van Eck, M; Rye, KA; Bursill, CA; Tas, SW; De Winther, MPJ; Biessen, EAL; Donners, MMPC
Abstract: High-Density Lipoproteins (HDLs) have potent anti-inflammatory effects in various cell types. However, little is known about effects of HDLs on macrophages, key immune cells in atherosclerosis. In this study we aim to elucidate HDLs effects on macrophage inflammatory responses. Pre-incubation of human and murine macrophages with human reconstituted (apolipoproteinA-I/phosphatidylcholine) or native HDLs significantly decreased LPS-induced anti-inflammatory IL-10 production, while the opposite was observed for the pro-inflammatory mediators IL-12 and TNF-α. These pro-inflammatory effects were confirmed in vivo in peritoneal macrophages of human ApoA-I transgenic mice, which have high circulating HDLs levels. Stimulation with TLR7 ligand R848 showed similar effects both in vitro and in vivo, indicating that the observed effects are not TLR4 specific. Luciferase reporter assays and NF-κB target gene expression analyses showed that the pro-inflammatory HDLs effects in macrophages were mediated by NF-κB. However, IKK2-/- and NIK-/- macrophage HDLs responses are similar to wildtypes, i.e. excluding the IKK2-dependent canonical as well as the NIK-dependent non-canonical pathway. The pro-inflammatory activity of HDLs in macrophages was not attributable to ABCA1, ABCG1, SR-BI or CD36, established HDLs receptors, as HDLs show equivalent effects in macrophages from the respective knockout mice. Nevertheless, pre-treatment with β-methyl cyclodextrin abrogated the HDLs response, indicating that the pro-inflammatory effects are mediated by cholesterol depletion from macrophages. Although HDLs have been shown to exert anti-inflammatory functions in various cell types, our data point to pro-inflammatory effects of HDLs on macrophages in vitro and in vivo. Such detrimental effects on macrophages might limit the therapeutic potential of HDLs.